Maternal Caffeine Consumption and Racial Disparities in Fetal Telomere Length - Isabel Griffin, MPH; Boubakari Ibrahimou, PhD; Natasha Navejar, BS; Anjali Aggarwal, MD; Kristopher Myers, MPH; Daniel Mauck, MPH; Korede K. Yusuf, MBBS, PhD; Usman J. Wudil, MD, MPH; Muktar H. Aliyu, MD, DrPH; Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2019)
Background and Objectives: The identification of risk factors for shorter telomere length, especially during fetal development, would be important towards caffeine consumption recommendations for pregnant women on a global scale. The purpose of this study was to evaluate the association between caffeine intake and fetal telomere length as well as racial/ethnic differences in telomere length regardless of maternal caffeine consumption status. Methods: Caffeine intake was measured using a food frequency questionnaire (FFQ). Three generalized linear models (GLM) were compared based on binary categorical variables of caffeine levels using data mean value of 117.3 mg as cut-off; the World Health Organization (WHO) recommendations of 300 mg; and the American College of Obstetricians and Gynecologists (ACOG) recommendations of 200 mg. The association between caffeine consumption and telomere length (telomere to single-copy [T/S] ratio) was then assessed. Results: Among 57 maternal-fetal dyads, 77.2% reported less than 200 mg of caffeine (ACOG) and 89.5% less than 300 mg (WHO). Both WHO and ACOG models found that caffeine intake was significantly and positively associated with longer telomere length (p<0.05); and sodium (p<0.05). Other" race (p<0.001) and "white" race (p<0.001) were also significantly and positively associated with longer telomere length in the same models. Increasing maternal age shortened telomere length significantly in all models (p<0.001). Conclusion and Global Health implications: Caffeine intake, maternal age, and race may be associated with alterations in fetal telomere length. This indicates that caffeine consumption during pregnancy may have long-term implications for fetal development. The racial/ethnic differences in telomere length found in this study warrant larger studies to further confirm these associations. Key words: • Telomere • Fetal telomere length • Caffeine • Pregnancy • Maternal-Fetal medicine • Racial/ethnic differences   Copyright © 2020 Griffin et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.